Characterizations of synthesized laser scribed graphene/molybdenum disulfide (LSG/MoS2) hybrids for supercapacitor performance - Mugashini Vasudevan; Aiswarya Kanesan; Sathaniswarman Remesh; Veeradasan Perumal; Pandian Raja; Mohamad Nasir Mohamad Ibrahim; Saravanan Karuppanan; Subash Gopinath; Mark Ovinis (Journal of Water and Environmental Nanotechnology)
The purpose of this research is to develop a sustainable and organic energy storage system from oil palm lignin waste-derived Laser Scribed Graphene embedded with molybdenum disulfide (LSG/MoS2). In this study, LSG/MoS2 hybrids were fabricated to overcome the graphene zero band gap, restacking issues of molybdenum disulfide and to induce the electrical conductivity. Therefore, various amounts of LSG (0.1,0.5,1.0 g) were added in MoS2 precursor to produce nanoscale LSG/MoS2 hybrid nanostructure via the hydrothermal method. To justify the findings of LSG/MoS2 hybrid nanostructures, Raman spectroscopy, FESEM, TEM, and XRD were conducted. The D, G and 2D bands found in LSG confirm the formation of graphene from lignin. The morphology of LSG/MoS2 hybrids is porous and has a large surface area anchored with 3D MoS2 nanoflower on LSG. TEM has proved that LSG was wrapped with MoS2, where the presence of lattice spacing of 0.62 and 0.27nm, which corresponded to the (002) and (100) planes of MoS2 was observed. The electrochemical performance of the hybrids was conducted through Electrochemical Impedance Spectroscopy (EIS) demonstrated that increment in LSG in MoS2 precursor effects the impedance and resistances performances.